The implementation of Al-Quran and Fardhu Ain (KAFA) class teacher teaching practices in teaching Tajweed Al-Quran in Kedah - Muhammad Amirul Mohd Nor; Muhammad Zulazizi Mohd Nawi; Norhisham Muhamad (Journal of Research, Policy & Practice of Teachers & Teacher Education, 2021)
This study was conducted to identify the Implementation of Al-Quran and Fardhu Ain (KAFA) Class Teacher Teaching Practices in Teaching Tajweed Al-Quran in Kedah as prescribed by the Malaysian Teacher Standards (SGM). In general, the design of this study is a quantitative study and the research instrument used is in the form of a set of questionnaires. Also, the number of study samples taken is a total of 210 respondents consisting of male and female KAFA teachers in the state of Kedah. These quantitative data were analyzed descriptively and inferentially through SPSS software, version 22 to obtain frequency, percentage, mean, standard deviation, and t-test. Findings of the study showed that the implementation of KAFA teachers' teaching practices in teaching tajwid al-Quran in Kedah based on the components of the beginning of the teaching, development of teaching, and closing of teaching was at a moderate andhigh level (M=3.81, SD =1.02). While the inferential analysis found that there were no significant differences for teachers' teaching practiceson gender, place of residence, and course attendance. The implications of this study can be a guide to other teachers to improve teaching practices, especially in the field of tajwid Al-Quran that can produce effective and quality teaching. In essence, the quality of implementation of KAFA teachers' teaching practices in teaching tajwid al-Quran in the state of Kedah needs to be improved so that the excellence of KAFA education can be competitive on the international stage.